Analisis Wacana Kritis Norman Fairclough Pada Film Barbie 2023 Sebagai Representasi Budaya Patriarki - Putri, Rosalinda Mardiana; Mayasari, Mayasari; Nurkinan, Nurkinan (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Film is part of audio-visual mass media communication and aims to convey social messages to the audience in accordance with the reality that is growing and developing in society. One of the films that has this purpose is the film Barbie Live Action 2023. The purpose of this research is to dissect the discourse in three dimensions, namely textual, discourse practice, and sociocultural practice. In this research, the type of research used is qualitative-descriptive research. The paradigm used in this research is the critical paradigm. The appropriate research method used for this research is Norman Fairclough's Critical Discourse Analysis method. In the textual dimension, the linguistic tools of Diction, Cohesion, Modality and figure of speech metaphor are obtained. In the discourse practice dimension, at the production level the Barbie film is produced with two backgrounds, namely Barbieland and the real world, namely the city of Los Angles, United States with English language dialogue. At a text consumption level, the film is the highest-grossing box office film of all time with earnings of $1.45 billion. Sociocultural practices have 3 levels, namely situational, institutional and social levels. Situational Barbie script was written during the pandemic. For example, the film Barbie was a box office success in almost the entire world and became the hope of the global community regarding the end of the pandemic. Furthermore, at the institutional level, which includes the media, is Greta Gerwig herself as a film filmmaker. Warner Bros. is the production house for the 2023 Barbie Live Action film. Then there is Mattel as the company behind the production of Barbie dolls. Finally, at the social level, this film shows how patriarchy persists in reality, the social and cultural system of American society still adheres to patriarchal culture and neglects women's rights and protection.